Effectiveness of Prior Knowledge-based Flipped Learning strategy to increase students’ self-efficacy - Fitriani, Henni; Imanda, Riska; Juliana, Rona; Fakhrah, Fakhrah; Unaida, Ratna; Alvina, Sirry (International Journal of Trends in Mathematics Education Research, 2023)
This study aims to describe the effectiveness of the Prior Knowledge-based Flipped Learning strategy to increase students' self-efficacy in the learning process on Electrolyte and Non Electrolyte Solutions. This research was carried out in the even semester of 2022/2023 at SMA Negeri 1 Gandapura. The type of research conducted was experimental research using a nonequivalent control group design. The population of this study were all students of class X Science at SMA Negeri 1 Gandapura for the academic year 2022/2023 which consisted of 4 classes, namely classes X IPA 1, X IPA 2, X IPA 3, X IPA 4, with a total of 144 students. The sampling technique in this study was purposive sampling. The sample in this study was class X IPA 1 as the experimental class and X IPA 4 as the control class. The experimental class was treated using the flipped learning strategy while the control class was treated using the Student Teams Achievement Division (STAD) strategy. And the results of the expert validation test for the student's self-efficacy questionnaire obtained 24 questionnaire items with the conclusion that they were feasible to use. Testing students' self-efficacy questionnaires from the results of the Independent Sample T Test found that the Sig (2-tailed) value of students' self-efficacy was 0.091 0.05 for the experimental class and 0.094 0.05 for the control class. Based on the test results, it can be concluded that the Prior Knowledge-based Flipped Learning strategy and the STAD (Student Team Achievement Division) strategy are effective in increasing students' self-efficacy levels.